STANDARDIZATION OF BEST SOIL MEDIA AND TIME OF GUAVA PROPAGATION THROUGH CUTTINGS UNDER JAMMU SUB TROPICS - SOHNIKA RANI,; AKASH SHARMA,,; V. K. WALI,; PARSHANTBAKSHI,; K. MOHDILLYAS, (The Bioscan, 2015)
Soft wood cuttings of guava treated with 4000 ppm IBA were planted in polybags containing different soil media during June, July, August and September. It was observed that among all the media compositions i.e. vermiculite + FYM (1:1), perlite + FYM (1:1), sand + FYM (1:1), vermiculite + sand + FYM (1:1:1) and perlite + sand + FYM (1:1:1), vermiculite + sand + FYM (1:1:1) showed maximum rooted cuttings (78.69%), number of new shoots per plant (10.42), plant height (26.49 cm), number of leaves per plant (25.08) and stem thickness (1.14 cm) while, cuttings planted in perlite + sand + FYM (1:1:1) took minimum days to sprout (8.95) during15th to 21st of August. Therefore it may be concluded that guava cuttings planted in soil media of Vermiculite + sand +FYM (1:1:1) of August was found to be best suitable media for guava propagation.